Analisis kemampuan pemecahan masalah matematis siswa dalam menyelesaikan soal kontekstual berorientasi higher order thinking skills ditinjau dari adversity quotient - Diningtyas, Gusmiarni Wahyu; Rahmatina, Desi; Azmi, Roma Doni (Karoteh Utama, 2025)
Mathematical problem-solving ability is one of the essential competencies that vocational high school (SMK) students must possess to be prepared for the workforce. However, students' success in solving mathematical problems can be influenced by their Adversity Quotient (AQ), which reflects their resilience and response to challenges. This study aims to describe the mathematical problem-solving ability of vocational high school students in solving HOTS-oriented contextual problems in terms of their AQ. The study employed a descriptive qualitative approach with nine Grade 10 Accounting students categorized into three groups based on AQ levels: Climber, Camper, and Quitter. Data collection techniques included AQ questionnaires, written tests, and interviews based on Krulick and Rudnick’s problem-solving indicators. The results show that all Climber students were able to solve all three HOTS-oriented contextual problems and fulfilled all problem-solving stages. Camper students completed the first and second problems by fulfilling all stages, but failed to reach the final stage, reflect and extend, on the third problem. Meanwhile, Quitter students were unable to solve any of the three problems and failed to meet any problem-solving indicators. These findings indicate that the higher the students’ AQ, the better their ability to solve HOTS-oriented contextual problems.